Suplementação de levedura autolisada em dietas para leitões de diferentes categorias de peso na fase de creche - Nogueira, Bruna Dantas (2018)
The objective of this study was to evaluate the effects of supplementation with autolysed yeast in diets for piglets of different weight categories in the day care phase on performance, intestinal morphometry and immunohistochemistry, blood parameters, microbiological parameters and economic viability. A total of 480 piglets were distributed in a 3 x 2 factorial arrangement, with 3 levels of autolysed yeast addition (0, 0.4 and 0.8%) and 2 weight categories (light and heavy, 5.71 ± 0) , 21 kg and 6.99 ± 0.25 kg, respectively), considering the bay with 20 piglets as experimental unit. There was a significant interaction between levels of autolysed yeast and weight category in the period from 21 to 42 days of age, with heavy animals presenting higher daily gain when supplemented with levels of 0.4% and 0.8% of autolysed yeast. Heavy animals supplemented with 0.4% and 0.8% of yeast in the diet had a higher mucosal thickness, higher villus height in the duodenum and jejunum presented higher villus thickness and better villus ratio: crypt for animals supplemented with 0.8 % of autolysed yeast. Supplementation of autolysed yeast (0.4% and 0.8%) resulted in a higher number of mitotic cells (P <0.05) in the duodenum, and in jejunum supplementation in 0.8% resulted in a higher value for same variable in relation to the level of 0.4% and this higher than the treatment without inclusion of the additive. Dietary inclusion of autolysed yeast improves performance parameters in heavy piglets, as well as increases the number of cells in mitotic duodenum and jejunum, and decreases the concentration of leukocyte cells in heavy animals. The inclusion of autolysed yeast in the diet at levels of 0.4 and 0.8% was economically feasible.